1997
DOI: 10.1016/s0012-365x(96)00159-8
|View full text |Cite
|
Sign up to set email alerts
|

Choosability and fractional chromatic numbers

Abstract: A graph G is (a, b)-choosable if for any assignment of a list of a colors to each of its vertices there is a subset of b colors of each list so that subsets corresponding to adjacent vertices are disjoint. It is shown that for every graph G, the minimum ratio a/b where a, b range over all pairs of integers for which G is (a, b)-choosable is equal to the fractional chromatic number of G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 4 publications
3
64
0
Order By: Relevance
“…In Section 4 we exhibit examples such that certain coordinates have to be large for any vector x attaining the maximum in (1), that is, for any nonnegative integer-valued vector x with imp(…”
Section: Introductionmentioning
confidence: 99%
“…In Section 4 we exhibit examples such that certain coordinates have to be large for any vector x attaining the maximum in (1), that is, for any nonnegative integer-valued vector x with imp(…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in Introduction Section, Alon et al [1] showed that the fractional chromatic number and the list fractional chromatic number are the same. Here, we follow the lines of their proof and show that the fractional chromatic and the measurable list chromatic numbers are the same.…”
Section: Fractional Coloringsmentioning
confidence: 91%
“…A list variant of fractional colorings was studied by Alon et al [1]. Fix a graph G. For each positive integer q, let p q be the smallest integer such that if every vertex v is assigned a list L(v) of p q colors, then there exists a q-coloring c of G with c(v) ⊆ L(v).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the fractional chromatic number and the fractional list chromatic number of a graph are always equal [8] (also see [12,Theorem 3.8.1]), it follows that any such precoloring can be extended for ε ≥ 1 if d ≥ 3; thus, the minimum value is always at most one.…”
Section: Problemmentioning
confidence: 99%